EXTERNAL GENITAL ENDOMETRIOSIS (CLINICAL CASE) - Fetishcheva, Larisa Egorovna; Petrich, Lyubov Nikitichna; Lavrova, Elizaveta Vladimirovna; Akhmadeeva, Alena Ramilovna; Rudaeva, Elena Vladimirovna; Moses, Vadim Gelievich; Elgina, Svetlana Ivanovna; Moses, Kira Borisovna (Mother and Baby in Kuzbass, 2026)
Endometriosis is a common disease that occurs regardless of ethnicity, race, socioeconomic status, and age. This condition is characterized by the proliferation of endometrial tissue outside the uterine cavity, causing chronic pelvic pain, abnormal uterine bleeding, infertility, dysfunction of adjacent organs, and other complaints that reduce quality of life. Endometriosis remains one of the most socially and demographically significant diseases, requiring a multidisciplinary approach. This article describes a rare clinical case of severe external genital endometriosis. Thanks to the multidisciplinary approach of obstetricians and gynecologists and the optimal management strategy chosen, a favorable outcome was achieved for the woman.